DESIGN OF COMBINATION BETWEEN WINDOWS NT SERVER WITH NETWARE SERVER - Devi Dimitra; Soebiyantiri, Ssi, MMEng Soebiyantiri, Ssi, MMEng (Jurnal Sistem Informasi, 1998)
A large company will have a subsidiary that uses computer networks with different operating systems. For example, two related subsidiaries are physically in a network but has a different network operating systems, PT "A" uses the operating system of Windows NT, and PT "B" using Novell NetWare. The merger between the two networks can be beneficial part companies, because with the merger can maximize the usefulness of existing resources within these two networks.